Perubahan dan Implikasi Susunan Organisasi dan Kewenangan Majelis Permusyawaratan Rakyat Setelah Amandemen UUD 1945 - Tenang Haryanto; Sri Hartini; Muhammad Toufik; Krisnhoe Kartika (Universitas Muhammadiyah Purwokerto, 2022)
The organizational structure of the MPR based on the amendments to the 1945 Constitution consists of members of the DPR and members of the DPD. Membership of the MPR is similar to the membership of Congress in the United States, which consists of the House of Representatives (lower house) and the Senate (high house). The authority of the MPR after the amendment of Article 3 of the Constitution of the MPR is no longer the highest state institution, but is a state institution whose position is equal to other state institutions. The purpose of this paper is to examine the changes in the organizational structure and authority of the People's Consultative Assembly after the amendment to the 1945 Constitution and what are the implications for changes in the organizational structure and authority of the MPR after the amendment. This research uses a statue approach. Data sourced from primary and secondary legal materials were analyzed using qualitative normative analysis methods. The results of the study found that after the amendment to the 1945 Constitution, the concept of the MPR as the holder of people's sovereignty was abolished. The MPR no longer holds the highest power in the state administration system in Indonesia. The implications of changes after the amendment to the Constitution, the role of the MPR is only limited to carrying out the task of socializing the results of the amendments to the 1945 Constitution and inaugurating the President and Vice President.Keywords: Organizational structure, Authority, MPR